2006
DOI: 10.1158/1078-0432.ccr-05-0331
|View full text |Cite
|
Sign up to set email alerts
|

The Schedule-Dependent Effects of the Novel Antifolate Pralatrexate and Gemcitabine Are Superior to Methotrexate and Cytarabine in Models of Human Non-Hodgkin's Lymphoma

Abstract: Purpose: Methotrexate is known to synergize with cytarabine [1-h-D-arabinofuranosylcytosine (ara-C)] in a schedule-dependent manner. The purpose of this article is to compare and contrast the activity of pralatrexate (10-propargyl-10-deazaminopterin)/gemcitabine to the standard combination of methotrexate/ara-C and to determine if schedule dependency of this combination is important in lymphoma. Experiment Design: Cytotoxicity assays using the standard trypan blue exclusion assay were used to explore the in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 23 publications
3
52
0
Order By: Relevance
“…This pattern of activity was observed in B-and T-cell lymphomas, both in vitro and in vivo. 9,10 Recent studies have established that pralatrexate synergizes with gemcitabine and that this synergy is superior to traditional MTX plus cytarabine. 10 With this rationale, a phase II study of pralatrexate (135 mg/m 2 every other week [QOW]) was initiated in patients with relapsed/ refractory lymphoma.…”
Section: Journal Of Clinical Oncologymentioning
confidence: 99%
See 1 more Smart Citation
“…This pattern of activity was observed in B-and T-cell lymphomas, both in vitro and in vivo. 9,10 Recent studies have established that pralatrexate synergizes with gemcitabine and that this synergy is superior to traditional MTX plus cytarabine. 10 With this rationale, a phase II study of pralatrexate (135 mg/m 2 every other week [QOW]) was initiated in patients with relapsed/ refractory lymphoma.…”
Section: Journal Of Clinical Oncologymentioning
confidence: 99%
“…9,10 Recent studies have established that pralatrexate synergizes with gemcitabine and that this synergy is superior to traditional MTX plus cytarabine. 10 With this rationale, a phase II study of pralatrexate (135 mg/m 2 every other week [QOW]) was initiated in patients with relapsed/ refractory lymphoma. This phase II study, which used the maximumtolerated dose (MTD) identified in patients with non-small-cell lung cancer, 11,12 revealed a higher incidence of stomatitis in patients with lymphoma.…”
Section: Journal Of Clinical Oncologymentioning
confidence: 99%
“…1,[4][5][6][7] The single drug regimen, such as liposomal DOX, 1,8 gemcitabine (GEM), [9][10][11][12][13][14] and liposomal VCR, 1,15 has been proven to treat B-cell lymphoma in clinical trials. Based on their (DOX, GEM and VCR [DGV]) different mechanisms of action, the combination chemotherapies of DGV are effective and well tolerated in relapse and refractory NHL.…”
Section: Introductionmentioning
confidence: 99%
“…It is already known that methotrexate synergizes with cytarabine (1-h-D-arabinofuranosylcytosine [ara-C]) in a schedule-dependent manner. Toner and colleagues [Toner et al 2006] compared the activity of pralatrexate plus gemcitabine with the standard combination of methotrexate plus ara-C. The study demonstrated that the combination of pralatrexate followed by gemcitabine was superior to methotrexate/ara-C in the in vitro and in vivo models and was far more potent in inducing apoptosis in DLBCL.…”
Section: Pralatrexate Used In Combinationmentioning
confidence: 99%